Light and productivity of Antarctic phytoplankton during austral summer in an ice edge region in the Weddell-Scotia Sea - Figueiras, F. G.; Pérez, Fiz F.; Pazos, Yolanda; Ríos, Aida F. (Journal of Plankton Research, 1994)
21 páginas The photosynthesis-irradiance relationships (P-I curves) of natural plankton samples were studied in the Weddell Sea ice-edge zone, between Elephant Island and South Orkney Islands, during the austral summer of 1988–89. Three water bodies were distinguished in the region: Bellingshausen Sea waters modified after flowing through Drake Passage and Bransfield Strait, Weddell Sea waters and Weddell Sea waters modified by melting. The stations situated in modified Bellingshausen waters showed a net phytoplankton composition which was different from that of the other two water bodies. Weddell Sea waters and Weddell Sea waters modified by melting of sea ice had the same net phytoplankton composition. In the area of modified Weddell Sea waters, there was an accumulation of phytoplankton in the upper 40 m (>4 mg Chl m−1). pB, and α were independent of depth, but varied between stations. The P-I parameters exhibited an east-west gradient with the maximum values in the Elephant Island region, where large diatoms were absent. The light-saturation parameter Ik averaged 35 ± 13 μmol m−2 s−1. The mean irradiance of the upper mixed layer was 34±13 μmol m−2 s−1, thus virtually equal to Ik. These results are discussed in the context of critical depth (Zc, net compensation irradiance (In) and depth of the upper mixed layer (Zuml). We suggest that the phytoplankton in the region is adapted to maximize its carbon uptake and growth rate at the mean irradiance of the upper mixed layer (Iuml) in well-mixed zones. We also suggest that the light-saturation parameter (Ik) could be the irradiance at which photosynthesis approximately compensates the total losses of the community (In). Peer reviewed